Pseudolymphomatous Folliculitis on the Nose - Aya Kakizaki; Taku Fujimura; Ikuko Numata; Akira Hashimoto; Setsuya Aiba (Karger Publishers, 2012)
Pseudolymphomatous folliculitis (PLF), which sometimes mimicks cutaneous lymphoma, is a rare manifestation of cutaneous pseudolymphoma and cutaneous lymphoid hyperplasia. We describe a 57-year-old Japanese woman with PLF on the nose that resembled cutaneous lymphoma clinically. The biopsy specimen revealed dense lymphocytes, especially CD1a+ cells, infiltrated around the hair follicles. Without any additional treatment, her nodule rapidly decreased before we performed a second biopsy for analysis of the clonal gene rearrangement. Though PLF typically behaves as benign lymphohyperplasia, differentiation from cutaneous lymphoma is necessary.